2021
DOI: 10.1007/s00405-021-06643-6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual voice clinics in the COVID-19 era: have they been helpful?

Abstract: Purpose In response to the coronavirus pandemic, a tertiary combined Laryngology-Speech Therapy voice clinic was converted to a wholly virtual clinic, with consultations carried out via telephone or video. The aim of our mixed method study was to assess (a) how effective are virtual clinics vs face-to-face clinics in progressing patients’ care and (b) what is patient satisfaction with virtual consultation methods. Methods Analysis of clinic data from patient databases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Convenience was most often reported, from the citizens’ perspective, as an advantage of relocating care. This was true for all forms of relocation [ 27 30 , 32 34 , 38 , 41 , 42 , 45 , 47 , 49 , 52 54 , 58 60 , 65 67 , 69 , 70 , 73 , 78 , 82 , 84 86 , 88 , 90 , 93 , 94 ]. Citizens think of relocating as convenient because in most cases it saves travel time [ 26 , 29 , 53 ].…”
Section: Resultsmentioning
confidence: 74%
“…Convenience was most often reported, from the citizens’ perspective, as an advantage of relocating care. This was true for all forms of relocation [ 27 30 , 32 34 , 38 , 41 , 42 , 45 , 47 , 49 , 52 54 , 58 60 , 65 67 , 69 , 70 , 73 , 78 , 82 , 84 86 , 88 , 90 , 93 , 94 ]. Citizens think of relocating as convenient because in most cases it saves travel time [ 26 , 29 , 53 ].…”
Section: Resultsmentioning
confidence: 74%
“…A recent study showed there is limited value in assessing voice disorders over the telephone. 10 Clinicians can easily misjudge the severity of hoarseness during a telephone consultation and offer these patients deferred appointments. Future studies could examine associations between presenting symptoms and late diagnoses in urgent head and neck cancer telephone clinics on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that virtual methods of consultation are valuable and can meaningfully progress patient care [ 16 ]. Furthermore, studies investigating patient experience with teleconsultation have shown a generally high degree of patient satisfaction [ 12 , 16 ]. In our cohort, we found a positive patient engagement with this hitherto unconventional method of consultation.…”
Section: Discussionmentioning
confidence: 99%